Numerical simulation based on a weakly compressible model in the multi-elbow pipe - Lin, Peifeng; Kang, Xuefeng; Huang, Ruijian (Frontiers in Energy Research, 2023)
The accuracy of pipeline leak detection and location is a very important aspect of practical engineering applications. In this paper, a new method based on a weakly compressible model and a standard k-e turbulence model is proposed. The method is used to simulate the propagation of negative pressure waves in the pipe. The results show that the propagation velocity of negative pressure waves in the elbow is 1.4% higher than in the straight pipe. It is found that the backflow phenomenon exists in each elbow, which affects the propagation distance of the negative pressure wave at different locations in the elbow. The vortex viscosity and turbulence frequency in the elbow axis are 12.2% and 5.4% higher than those in the straight pipe, respectively. In addition, the high viscous forces and pulsation frequency in the elbow accelerate the volumetric compression and expansion of the flow elements. For this reason, the equivalent length equation of the elbow in the negative pressure wave leakage localization method is proposed to verify the applicability of the weakly compressible model.